2021
DOI: 10.1111/all.14776
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells: The missing part of a puzzle in food allergy

Abstract: Food allergy is an increasingly prevalent disease driven by uncontrolled type 2 immune response. Currently, knowledge about the underlying mechanisms that initiate and promote the immune response to dietary allergens is limited. Patients with food allergy are commonly sensitized through the skin in their early life, later on developing allergy symptoms within the gastrointestinal tract. Food allergy results from a dysregulated type 2 response to food allergens, characterized by enhanced levels of IgE, IL‐4, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 149 publications
(359 reference statements)
0
26
0
1
Order By: Relevance
“…On the other hand, IL-1beta and IL-23 drive Th17 cell polarization [28]. Cheungi et al suggested that IL-17A and IL-17F may promote the formation of eosinophils, as well as increase the levels of IL-1beta and IL-23 [79]. These findings support the interaction between eosinophils and Th17 cells in the pathogenesis of atopic disorders.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, IL-1beta and IL-23 drive Th17 cell polarization [28]. Cheungi et al suggested that IL-17A and IL-17F may promote the formation of eosinophils, as well as increase the levels of IL-1beta and IL-23 [79]. These findings support the interaction between eosinophils and Th17 cells in the pathogenesis of atopic disorders.…”
Section: Discussionmentioning
confidence: 88%
“…Also, TSLP have been shown to activate ILC2 in esophageal lymphoid tissue in EoE. 45 MMP10 has been shown to be important in airway remodeling and inflammation by regulating macrophage activity. 46 Increased expression of MMP10 are found in patients with high levels of eosinophils in the bronchial submucosa 47 and in severe asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…The precursor cells of mast cells are derived from haematopoietic stem cells and migrate into tissues along with blood to complete the differentiation process (Tanaka, 2020). They are involved in regulating the integrity of the intestinal mucosa and the barrier of the epithelium and are crucial to maintain homeostasis in intestine (Sahiner et al, 2021). Our study found that alpaca mast cells were mainly distributed in the lamina propria and submucosa, with abundant particles in the cytoplasm, and the granular material released was observed in the interstitial space.…”
Section: Discussionmentioning
confidence: 99%